2013
DOI: 10.1371/journal.pone.0061604
|View full text |Cite
|
Sign up to set email alerts
|

Association between Myocardial Triglyceride Content and Cardiac Function in Healthy Subjects and Endurance Athletes

Abstract: Ectopic fat accumulation plays important roles in various metabolic disorders and cardiovascular diseases. Recent studies reported that myocardial triglyceride (TG) content measured by proton magnetic resonance spectroscopy (1H-MRS) is associated with aging, diabetes mellitus, and cardiac dysfunction. However, myocardial TG content in athletes has not yet been investigated. We performed 1H-MRS and cardiac magnetic resonance imaging in 10 male endurance athletes and 15 healthy male controls. Serum markers and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
(49 reference statements)
2
23
0
2
Order By: Relevance
“…In previous reports, the myocardial TG content has been shown to positively correlate with LV mass weight per LV volume according to the degree of LV hypertrophy (4). Furthermore, we recently reported that athletes exhibit lower myocardial TG levels (13). We also included several endurance athletes in the present study; however, similar trends were obtained after excluding these subjects (data not shown).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In previous reports, the myocardial TG content has been shown to positively correlate with LV mass weight per LV volume according to the degree of LV hypertrophy (4). Furthermore, we recently reported that athletes exhibit lower myocardial TG levels (13). We also included several endurance athletes in the present study; however, similar trends were obtained after excluding these subjects (data not shown).…”
Section: Discussionsupporting
confidence: 78%
“…Cardiac magnetic resonance imaging (MRI) and 1 H-MRS were conducted on a MAGNETOM Avanto 1.5-Tesla MRI system (Siemens Medical Solution, Erlangen, Germany), as previously reported (13). In brief, each subject rested in the supine position with a belt placed around the upper part of the abdomen in order to minimize respiratory movements.…”
Section: Mri and Mrsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using proton magnetic resonance spectroscopy ( 1 H-MRS), Sai et al [144] demonstrated a marked reduction in myocardial triglyceride content and a significant improvement in cardiac function in endurance athletes who were exercising for 5 days a week. In contrast, Schrauwen-Hinderling et al [145] showed that combined endurance and strength training 3 times per week for 12 weeks improved insulin sensitivity, VO 2max , LVEF and cardiac output in obese T2DM individuals without altering the cardiac lipid content.…”
Section: Exercise-mediated Cardioprotectionmentioning
confidence: 99%